The Relationship of Preeclampsia and Eclampsia, Antepartum Haemorrhage and Anemia Mother with Apgar Score - Rahman, Mahy Ragib; Ngo, Novia Fransiska; Wardhana, Ahmad Wisnu (Jurnal Kesehatan Pasak Bumi Kalimantan, 2022)
Background: Everyday 7,000 babies die worldwide, with 2,4 million babies dying in the first month of life. While in Indonesia 19 deaths per 1000 live births with the main causes of neonatal death in 2017 were complication related to premature birth (asphyxia or difficulty breathing at birth), infections, and births defects. Meanwhile, in East Kalimantan, the highest cause of death was dominated by low birth weight (LBW) followed by asphyxia neonatorum. The examination that is always used in newborns by health workers to assess the occurrence of distress respiration neonatal is to assess the APGAR score. The APGAR score reflects clinical signs of distress respiration neonatal, such as cyanosis or pallor, bradycardia, reflex response to stimuli, hypotonia, and apnea or dyspnea. Scores will be reported within the first minute and fifth minute after birth for all infants and thereafter at intervals of 5 minutes to 20 minutes for infants with a score below 7 (asphyxia). Preeclampsia and eclampsia, antepartum haemorrhage, and maternal anemia are factors that can affect the APGAR score which is one of the assessments of the diagnosis of neonatal asphyxia. Research Objectives: to determine the relationship between risk factors and APGAR scores below 7 (asphyxia) in Abdoel Wahab Sjahranie Hospital, Samarinda. Methods: The design of this study used case control using observational analytical methods. The sample was taken from the medical record data of mothers and children born at the Abdoel Wahab Sjahranie Hospital Samarinda for the 2019-2021 period as many as 65 cases and 65 controls. Result: Bivariate analysis was performed using the chi-square test. The results of the analysis showed that there was a relationship between preeclampsia (p=0.000), eclampsia (p=0.003), antepartum bleeding (p=0.001), and anemia (p=0.001) with an APGAR score below 7.Keywords:  APGAR score, preeclampsia, eclampsia, anemia, haemorrhage, asphyxia.